Proteomic profiles of young adults with acute myocardial infarction - Mohamed Bakrim, Norbaiyah; Mohd Shah, Azarisman Shah; A.Talib, Norlelawati; Ab Rahman, Jamalludin; Muhamad Bunnori, Noraslinda; Idorus, Mohd Yusri; Zainal Abidin, Siti Khairani; Abdullah, Aszrin (Kulliyyah of Medicine, International Islamic University Malaysia, 2019)
Introduction: Proteomic profiling is essential in understanding the pathophysiological process of multifactorial diseases such as acute myocardial infarction (AMI). Despite the increasing incidence of AMI in young adults, proteomic-based study focusing on young AMI remains limited. This study aimed to examine the plasma proteomic profiles of young adults with AMI compared to control subjects. We also hope to identify disease-specific protein biomarkers that contribute to the development of AMI in the young. Methods: Pooled plasma protein from 10 AMI patients aged 18 to 45 years and 10 age, gender and racematched volunteers were separated using two-dimensional electrophoresis (2-DE). The spots proteins were analysed using the PD Quest analysis software. The spots proteins that were found to have been expressed differently between the two groups were identified by Matrix Assisted Laser Desorption/Ionization Time of Flight (MALDI-TOF) Mass Spectrometry. Results: There were three differently expressed proteins namely Apolipoprotein AI (Apo AI), Apolipoprotein AIV (Apo AIV) and Haptoglobin (p < 0.05). The expressions of these proteins were found to be increased in young patients with AMI compared to control subjects. Conclusion: The up regulation of Apo AI, Apo AIV and Haptoglobin in AMI patients indicate their important roles in the development of atherosclerotic disease. Thus, Apo AI, Apo AIV and Haptoglobin are potential disease biomarkers for young AMI.